DESKRIPSI KETERLIBATAN ORANG MUDA KATOLIK DALAM HIDUP MENGGEREJA: Studi Kasus pada Sanggar Emaus Paroki Santo Petrus Kanisius Wonosari - Jatmiko, Benedictus Herdiawan Budi; Wulung, Heryatno Wono (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
Nowadays, young Catholics are seen as having a more important role in church life. Based on this, each parish has its way of encouraging Catholic Youth to be involved in church life. Therefore, this article aims to get an overview of the involvement of Catholic Youth in church life and the dynamics that occur in Sanggar Emaus. This research uses a qualitative approach with data collection techniques through observation, questionnaires, and interviews. The results showed that the Catholic Youth in St. Peter Kanisius Wonosari Parish who often gather in Sanggar Emaus are not fully involved in church life. Most of them involve themselves only within the scope of the parish church. The church life seen in Young Catholic of Wonosari Parish is more dominant by involving their activities in the field of liturgy and coinonia. Meanwhile, Sanggar Emaus is the centre of involvement of Young Catholics of Wonosari Parish, especially those who live within the city area. The dynamics in Sanggar Emaus are fluid, there are no binding rules, and activities are carried out according to the wishes of young people. Sanggar Emaus can be a model of informal mentoring with a pleasant atmosphere so it is expected to encourage Catholic Youth to play an active role in church life.